Nuciferine downregulates Per-Arnt-Sim kinase expression during its alleviation of lipogenesis and inflammation on oleic acid-induced hepatic steatosis in HepG2 cells - Zhang, Dan-Dan; Zhang, Ji-Gang; Wu, Xin; Liu, Ying; Gu, Sheng-Ying; Zhu, Guan-Hua; Wang, Yu-Zhu; Liu, Gao-Lin; Li, Xiao-Yu (Frontiers in Pharmacology, 2015)
Nonalcoholic fatty liver disease (NAFLD) is a prevalent liver disease associated with lipotoxicity, lipid peroxidation, oxidative stress and inflammation. Nuciferine, an active ingredient extracted from the natural lotus leaf, has been reported to be effective for the prevention and treatment of NAFLD. Per-Arnt-Sim kinase (PASK) is a nutrient responsive protein kinase that regulates lipid and glucose metabolism, mitochondrial respiration and gene expression. The aim of the present study was to investigate the protective effect of nuciferine against NAFLD and its inhibitory effect on PASK, exploring the possible underlying mechanism of nuciferine-mediated inhibition on NAFLD. Relevant biochemical parameters (lipid accumulation, extent of oxidative stress and release of inflammation cytokines) in oleic acid (OA)-induced HepG2 cells that mimicked steatosis in vitro were measured and compared with the control. It was found that nuciferine and silenced-PASK (siRNA PASK) both inhibited triglyceride (TG) accumulation and was effective in decreasing fatty acid (FFAs). The content of total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) were increased respectively by nuciferine and siRNA PASK without increase in glutathione (GSH). Malondialdehyde (MDA) was decreased respectively by nuciferine and siRNA PASK. In addition, nuciferine decreased TNF-a, IL-6 and IL-8 as well as the siRNA PASK group. IL-10 was increased by nuciferine and siRNA PASK respectively. Further investigation revealed that nuciferine and siRNA PASK could respectively regulate the expression of target genes involved in lipogenesis and inflammation, suggesting that nuciferine may be a potential therapeutic treatment for NAFLD. Furthermore, the modulated effect of nuciferine on (OA)-induced HepG2 cells lipogenesis and inflammation, which was accompanied with PASK inhibition, was also consistent with siRNA PASK, implying that PASK might play a role in nuciferine-mediated regulation on NAFLD.